An Evaluation of the Implementation of ICT Framework in Jigawa State: A Case Study of Galaxy Backbone Dutse - Alhaji Ibrahim, Muhammad; Shu'aibu, Ibrahim; Abdullahi Namadi, Hajara; Meiwanto Doktoralina, Caturida; Mulya, Imam (KnE Social Sciences, 2023)
Rapid development in information and communication technology (ICT) has basically transformed the process and procedure of almost all forms of endeavour within health, education, business, governance, and civil service. Despite the devastating impact of Covid-19 pandemic on world economy, schools closure, businesses, and social activity, the information and communication technology has enhanced economic growth, generated business opportunities and employment, provided effective productivity and enhanced social and government services during the pandemic. The main objective of this study is to evaluate the implementation of ICT framework in Jigawa State. The study employed qualitative case study, where a sample of 20 staff were purposely selected to participate in the study. The findings of the study revealed that the state government has adequately provided physical infrastructural development for the take up of Galaxy Backbone. The government payroll and integrated financial management information system was fully computerized. Surprisingly, the assessment showed that no single amount of money was generated through ICT in the state, and that their target of becoming regional hub for software development and hardware assembling were not achieved. Based on the above findings, recommendations were put forward to the state government that the implementation of ICT framework in the state should be reviewed in order to meet the set target and a trained and professional ICT expert should be employed in the agency to guide the implementation and achievement of the set target. Keywords: ICT, evaluation, ICT framework, model of evaluation, CIPP model